Health and social care professionals’ awareness and implementation of NICE guidelines on self-harm: a rapid review of the literature - Dawn Dowding; Christopher J Armitage; Gill Lever; Dharman Jeyasingham (BMJ Open)
Objectives To identify the factors influencing professionals’ implementation of the National Institute for Health and Care Excellence (NICE) guidelines on self-harm.Design A rapid review evidence synthesisData sources Five electronic databases (ASSIA, CINAHL, EMBASE, MEDLINE, PsycINFO) and five indexing databases (Science Citation Index Expanded (SCIE), Social Sciences Citation Index (SSCI), Arts and Humanities Citation Index (AHCI), Emerging Sources Citation Index (ESCI) and Conference Proceedings Citation Index (CPCI)), using the Web of Science platform, were searched in December 2023 and repeated in July 2024.Eligibility criteria We included quantitative and qualitative studies that investigated professionals’ knowledge and implementation of NICE guidelines on self-harm, that were in English language and published between 2004 and July 2024.Data extraction and synthesis One reviewer used standardised methods to search, screen, select, quality assess and synthesise the included studies, to accelerate the review. Quality assessment was conducted using the Mixed Methods Appraisal Tool. Data were extracted and synthesised thematically using NICE guidance implementation priorities.Results The review included 10 studies. Six were conducted in accident and emergency (A&E) settings, two in general practice, one in a burns and plastic surgery hospital department and one involved cross-sectoral health professionals. Key findings indicate that awareness and implementation of self-harm guidelines is low among health professionals. Systemic barriers include lack of staff training, negative staff attitudes towards people who self-harm and lack of resources.Conclusions There is a need to develop and implement regular training on self-harm, incorporating NICE guidance and measures, to integrate knowledge and mobilise practice changes. Further research into the implementation of NICE guidelines in children who self-harm is needed, and in a wider variety of health and social care settings. The absence of studies from the social care sector into professionals’ awareness and implementation of NICE guidelines on self-harm is a key limitation.